Monetary Policy via Bank Lending Channel : Evidence from Lending Decomposition - PUTRA, PAMUNGKAS; Fadli, Septianto; Irwan, Trinugroho; Rossazana, Ab Rahim; Masagus, M. Ridhwan; Bruno S., Sergi (MDPI, 2025)
This paper examines the regional dimension of monetary policy transmission through the component of the bank lending channel in Indonesia. Understanding the effectiveness of this transmission channel at a regional level is crucial, given the diverse economic characteristics across Indonesian provinces. We employ panel regression to analyze the panel data consisting of provincial quarterly data from 2010–2023 for 33 provinces in Indonesia. The robustness of the results is further assessed through GMM estimation techniques. We find evidence of the bank lending channel through the use of the policy rate. Our findings are meaningful in the SME and consumer lending channel and are also more profound in Java than in the non-Java region. Further, using GMM estimation, we show that our results are robust. Our study highlights the significant role of regional differences in Indonesia when examining monetary policy effectiveness. Policymakers should therefore consider regional disparities and lending categories to enhance the efficacy of monetary policy interventions.